The fall of an inclined rod. (15th July 2021) - Cross, Rod
Abstract: If a rod is held almost vertically with one end at rest on a horizontal surface then it will fall to the surface when released. The rod might pivot about its bottom end or it might slide forwards or backwards on the surface, depending on the coefficient of friction. Experimental and theoretical results are presented for a rod with a spherical bottom end. In that case the rod rolls on its bottom end before sliding backwards and/or forwards. Results for a 1.0 m ruler are also presented.